Russia and Turkey in Nagorno-Karabakh, between militarization and diplomacy (Journal of the Spanish Institute for Strategic Studies, 2021)
On November 10, Russian president Vladimir Putin announced in a televised speech the ceasefire between Azerbaijan and Armenia, after weeks of fighting. With thousands of civilian and military casualties, the fight for control of the region of Nagorno-Karabakh is one of the frozen conflicts in the post-Soviet space. Its significance extends beyond the region, both because of the geostrategic importance of the South Caucasus, and because of the two actors that are present in the region, Russia and Turkey. This article seeks to analyze the Nagorno-Karabakh conflict as part of the foreign strategy of the Russian Federation, for which it is important to consider its relationship with Turkey in the Caucasus. But also in Syria, a scenario in which the two actors are currently fighting over the control of the territory.
Keywords: Russia, Turkey, Nagorno-Karabakh, Influence, Armenia, Azerbaijan, Syria